THE POSITION OF QIYÂS (ANALOGY) IN THE SHARIA ECONOMIC LAW AND ITS APPLICATION IN THE CONTEMPORARY BUSINESS TRANSACTIONS - Agus Putra, Panji Adam (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2024)
The agreed sources of law in Islamic law are the Holy Koran and the Sunnah. However, in the literature on ushul fiqh, Islamic jurists have different opinions regarding the position of analogy (qiyâs) as a source and legal proposition that functions as a method of finding law in Islam. Then there are differences of opinion regarding the use of analogy in the context of sharia economic law. This research focuses on the position of analogy (qiysâs) as a method of discovering sharia economic law and its application in the contemporary transactions. This study uses a qualitative method with a normative juridical approach. This research includes the type of literature study research. The results of the study show that analogy (qiyâs) can be used as a method of legal discovery, especially in sharia economic law and its application in contemporary transactions including qiyâs of IMFZ contracts to bai' al-salam contracts; (2) qiyâs sale and lease back transactions to bai' al-istighlâl; (3) qiyâs wakâlah bi al-ujrah contract to ijârah contract; (4) qiyâs Wada'i al-Mashrafiyyah to qardh contracts; and (5) qiyâs deposits to mudhârib-yudhârib.Keywords: Qiyâs, Sharia Economic Law, Legal Discovery Method